The rights of the child in voluntary care in Ireland: A call for reform in law, policy and practice. (June 2021) - Brennan, Rebekah; O'Mahony, Conor; Burns, Kenneth
Highlights: Voluntary care is a valuable pathway to care, but it needs to mitigate risks to children's rights. Some children in voluntary care receive inferior resources compared to children on care orders. Voluntary care in Ireland has weak mechanisms for ascertaining the views of the child. Children's assent should be sought for these agreements. Independent oversight of voluntary care agreements should be introduced. Abstract: Voluntary care agreements form a significant part of child protection systems in many jurisdictions. From a children's rights perspective, they enjoy numerous advantages over court-ordered removals of children. However, when loosely regulated, voluntary care agreements can give rise to significant concerns in respect of compliance with international children's rights law. This paper will present findings from the Voluntary Care in Ireland Study, one of the first in-depth empirical examinations internationally of voluntary care agreements. It will present qualitative data on the system in operation in Ireland that indicates that voluntary care agreements are less adversarial, time-consuming and costly than court proceedings. This frees up resources for early intervention and facilitates a more collaborative relationship between parents and social services, making it more likely that children will remain at home or eventually return home from care. At the same time, the findings suggest that the voluntary care system currently operated in Ireland suffer from numerous flaws, including absence of independent oversight; unlimited duration; potential instability (since parents can withdraw consent at any time); weak mechanisms for child participation; and inferior resource allocation compared to court-ordered care placements. The paper examines legislative provisions from a number of comparable jurisdictions and makes recommendations designed to ensure that the voluntary care system in Ireland complies more strongly with principles of international children's rights law.